Enhancing radiostrontium uptake by a pillared montmorillonite, modified by organic acids - Papachristodoulou, C. A.; Assimakopoulos, P. A.; Gangas, N.-H. J. (HNPS Advances in Nuclear Physics, 2019)
The possibility to increase strontium uptake by an aluminum pillared montmorillonite has been studied by introducing organic acids in the interlayer space of the PILC. The effect of the acid was found to depend on its acid strength and the pH of the exchange solution. Oxalic acid proved the most successful agent, leading to an increase in Sr2+ uptake ranging from 0.3 to 0.4 meq g"1 at pH«8, compared to the rest of the acids used. Furthermore, the amount of Sr2* ions retained by the PILC-oxalic acid sample, after decreasing the pH from 8 to 3, was measured to be higher by a factor of 9 compared to the unmodified material